PENERAPAN TEORI BELAJAR KONSTRUKTIV PEMBELAJARAN FIQIH TENTANG MAKANAN HALAL DAN HARAM MENGGUNAKAN MEDIA VIDEO DI KELAS VI MADRASAH IBDITAIYAH NEGERI 01 KOTA BENGKULU - Ilhamuddin; Satria, Irwan; Utami, Intan (Yayasan Darussalam Bengkulu, 2021)
The problem is to be less attractive in fiqih halal and haram in fiqih learning by using the lecture theory. So with this problem researchers are doing research using constructive study theory using video media. The study aims at the application of fiqih constructions of halal and haram learning using video media in the 01 state state of bengkulu. The study USES the PTK method (class action research). This research sample is 33 students. The value of teacher or researcher activity on cycle I is 77.5 and then in cycle ii increases to 87.5. Whereas the value of student activity on cycle I was 80 then in cycle ii increased to 87.5. It shows that the value of teacher and student activity is showing on very good kreteria. There is an increased motivation for learning in halal and haram learning materials in the classroom vi min 01 of bengkulu. At least a good category of student learning motivation presentation on the I cycle of 86.21% previously on pre-cycle implementation of only 25%, on cycle ii increased to 90%. This suggests that learners have had the high motivation to learn the fiqih subjects halal and haram food.